Pola Konsumsi Air Bersih Studi Kasus Pada MAN 1 Kota Payakumbuh - Harfa Sakri (Jurnal Talenta Sipil, 2023)
MAN 1 Payakumbuh is one of the educational institutions located in Payakumbuh. As an institution providing education with teaching and learning activities, MAN 1 Payakumbuh should be supported by adequate infrastructure and facilities, one of which is the availability of sufficient clean water. The increasing number of personnel at MAN 1 Payakumbuh from year to year, it is necessary to measure water consumption patterns. This research analyzed the number of personnel for the last five years and carry out calculations using standard usage in buildings in MAN 1 Payakumbuh . The results of this study concluded that there was an increase in water consumption patterns from year to year where in the 2018/2019 school year it was 8870 liters/day, the 2019/2020 school year was 9650 liters/day, the 2020/2021 school year was 10220 liters/day, the school year 2021/2022 is 10520 liters/day, for the 2022/2023 school year it is 10540 liters/day with an average water consumption pattern reaching 9960 liters/day. An increase in consumption patterns every year, this data can be used as a reference for the future so that in MAN 1 Payakumbuh there will be no water shortage crisis.